Bioequivalence of two tablet formulations of cefpodoxime proxetil in beagle dogs - Gao, Yan-Yan; Sang, Ka-Na; Li, Peng-Peng; Hao, Jie; Zhang, Cong; Li, Huan-Juan; Zhou, De-Gang (Frontiers in Veterinary Science, 2022)
The pharmacokinetic profiles and bioequivalence of two cefpodoxime proxetil tablets were investigated in Beagle dogs. A single-dose, four-way complete replication and crossover design was used in the present study. A total of 28 healthy Beagle dogs (half male and female) with an average body weight of 11.1 kg were randomly allocated to this study. A whole reference or test tablet containing the equivalent of 100 mg of cefpodoxime was administered orally to each dog. Serial plasma samples were collected, and cefpodoxime concentrations were determined by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS/MS). Then a non-compartmental method was used to calculate the pharmacokinetic parameters of both tablet formulations. The average bioequivalence (ABE) or reference-scaled average bioequivalence (RSABE) methods were used to determine the 90% confidence interval (CI) of AUCINF_obs and Cmax. No significant differences were observed for both parameters between both tablets. The test formulation was bioequivalent to the reference one because the 90% CI ranges of Cmax and AUCINF_obs were all between 80 and 125%.